1703 The use of Inhaled Nitric Oxide in a Tertiary Paediatric Intensive Care Unit (PICU). (October 2012) - Durand, C; Mahoney, S; Kerr, S; Shetty, N; Buckley, D
Abstract : Aims: Inhaled nitric oxide (iNO) is used to reduce pulmonary vascular resistance and improve ventilation-perfusion mismatch. This study investigates the use of iNO in a tertiary PICU - Looking at evidence of objective assessment of its benefit (important for weaning/cessation of treatment). iNO costs £40/hour for the first 96 hours & free thereafter. Total spend in this tertiary Children's Hospital in the UK was approx £240, 000 per annum in 2010–11. Methods: All patients receiving iNO were identified. Data was collected prospectively from the bedside (hours on iNO) and retrospectively from case notes/electronic patient records. Results: 107 patient episodes were analysed; 63% were admitted for cardiac surgery and 66% received iNO for < 96hours. Analysis focused on 52 patients over 6 months. Indication for iNO was documented in 75% of cases; 48% of these patients had an echocardiogram prior to iNO. Of those in whom the indication was Pulmonary hypertension 65% had an echo, 35% had no echo. 52% of these were cardiac surgical patients. In those in whom the indication was low oxygen saturations 36% had an echo and 64% no echo. Oxygen saturations and objective improvement measures were not routinely recorded in patient records pre/post iNO. Conclusions: Main indications for iNO were pulmonary hyper-tension (36%) or low oxygen saturations (27%). 48% of patients didn't have an echo and oxygen saturations were not documented pre/post iNO. The use and effect of an expensive though potentially beneficial drug needs to be assessed and documented to justify its continued use.